Pemanfaatan Bioreaktor Mini Sebagai Alternatif Pengelolaan Sampah Berbasis Masyarakat Kelurahan Majahlega Kota Bandung - Wittesa, Chigara; Sutikno, Fauzul Rizal; Anggraeni, Mustika (Fakultas Teknik, Universitas Brawijaya, 2012)
The growth rate of population increase will be directly proportional to the increase in waste disposal. Increasing the volume of waste that is not followed by proper management can pose problems in handling waste. Bio Reactor Mini is one of the waste processing technology to reduce the volume of waste disposed to the landfills. This study aims to identify the operational performance of waste management on Bio Reactor Mini in Kelurahan Manjahlega Bandung City using Bio Reactor Mini erformance analysis, level of community participation analysis, institutional analysis, and level of community satisfaction using Important Performance Analysis (IPA). Based on the analysis of compliance with SNI 3242:2008, known that waste management using Bio Reactor Mini in Kelurahan Manjahlega obtain classification scores 20 are classified as Fit Waste Processing Standard In Settlement. Based on participatory analysis, derived categories partnership and co-learning. Based on the result of IPA, obtained by variable levels of perceived low community satisfaction. The result of this research is the recommendation about improvement Bio Reactor Mini performance, which consist of community participation,institutional, waste management system, so that the Bio Reactor Mini can be a system of community-based waste management.Keywords: Waste Management, Bio Reactor Mini, Community Participation